2010
DOI: 10.1680/gein.2010.17.5.344
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of permeability to gas of geosynthetic clay liners in unsaturated conditions

Abstract: International audienceThis paper is a contribution to the characterisation of permeability to gas of unsaturated GCLs, with applications in cover liners of municipal solid waste landfills. Conducting such tests at low gas pressure gradient limits the risk of moisture distribution change in the bentonite, which has been observed under high pressure gradients. However, a consequence of a low pressure gradient is a small gas flow rate that is difficult to measure with good accuracy. Therefore a solution may be th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This is because the high-quality sodium bentonite resources in China are scarce. Previous studies [11,12] found that the gas permeability of the sodium bentonite GCL decreased with increasing moisture content under different pressures. Studies have shown that the gas permeability changes after hydration from 1.0 × 10 −18 to 1.0 × 10 −11 m 2 [13][14][15].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…This is because the high-quality sodium bentonite resources in China are scarce. Previous studies [11,12] found that the gas permeability of the sodium bentonite GCL decreased with increasing moisture content under different pressures. Studies have shown that the gas permeability changes after hydration from 1.0 × 10 −18 to 1.0 × 10 −11 m 2 [13][14][15].…”
Section: Introductionmentioning
confidence: 88%
“…It can be observed that the moisture content of the clay enhanced as the content of ZP increased, while the gas permeability K p gradually decreased. The moisture content and gas permeability showed an apparent negative correlation, meaning that gas permeability decreased with the rise in moisture content [11][12][13]. When the ZP content was 1.0%, the gas permeability of the clay after drying was 1.12 × 10 −11 m 2 , which was 97% lower than that of the ZP admixture content of 0.2%.…”
Section: Gas Permeabilitymentioning
confidence: 94%
“…Earlier work has shown that the gas permeability of GCLs varied largely with changes in gravimetric moisture content as well as the form of bentonite (powdered or granular) used and indicated that very large attenuation of gas migration could occur if the GCL was sufficiently hydrated (Bouazza and Vangpaisal, 2003;Didier et al, 2000;Pitanga et al, 2011;Vangpaisal and Bouazza, 2004). More importantly, it was also reported that when a GCL lost the absorbed water, its gas permeability significantly increased because of shrinkage of the bentonite component and, in extreme cases, because of the formation of desiccation cracks that provided preferential gas flow paths Mendes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, there is a wide body of work available on their hydraulic performance in the context of landfill covers (Benson and Meer, 2009;Benson et al, 2007;Bouazza, 2002;Buckley et al, 2012;Rowe, 2013, 2014;LaGatta et al, 1997;Lin and Benson, 2000;Meer and Benson, 2007;Rowe, 2014;Rowe and Hosney, 2013;Scalia and Benson, 2011). However, experimental measurements of their permeability to gases are less widely available, and only recently has information on their advective gas flow performance became available in the context of landfill capping (Abuel-Naga and Bouazza, 2009;Bouazza and Vangpaisal, 2003Bouazza et al, 2008;Didier et al, 2000;Mendes et al, 2010;Pitanga et al, 2011;Vangpaisal and Bouazza, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations, the transient flow method has emerged as a successful alternative to estimate the hydraulic properties of low permeability materials such as rocks, soils (Haskett et al, 1988;Carles et al, 2007;Barral et al, 2009), concrete (Figg, 1973;Claisse et al, 2003), asphalt coating (Li et al, 2004) and bentonite geocomposite (Mendes et al, 2010;Pitanga et al, 2011).This method is essentially founded on monitoring of system's pressure drop as the gas passes through the permeable barrier. Therefore, compared with the conventional method for measuring permeability in a permanent flow regime, the pressure drop method seems to have advantages such as simplicity, economy and quick results.…”
Section: Introductionmentioning
confidence: 99%